Treatment of cancer associated anaemia - Rolski, Janusz; Pawlicki, Marek (Contemporary Oncology/Współczesna Onkologia, 2001)
Cancer associated anaemia is reported in 50% of cancer patients and life threating anaemia (Hb <6 g/dl) is observed in 8% of such patients. Etiopathogenesis of cancer associated anaemia was presented as well as early and late toxicity of blood transfusion. Erythropoietin treatment seems to be justified due to evident data suggesting quality of life and clinical response improvement related to anaemia cancer associated therapy. The most of patients respond to erythropoietin treatment and its cost are comparable with blood transfusions and post-transfusion toxicity treatment cost.